Exploring the potential of ume-derived proanthocyanidins: novel applications for blueberry preservation - Liang, Lishan; Qiu, Honghao; Liu, Yuntong; Liu, Yingjie; Weng, Luo; Zhong, Wenting; Meng, Fanxin (Frontiers in Microbiology, 2023)
Proanthocyanidins (PCs) extracted from ume have many well-known functional properties. The aim of this study was to explore a novel natural food preservative using Ume plum pulp proanthocyanidins (UPPP). The crude product of PCs from Ume plum was obtained by using ethanol as extraction solvent and ultrasonic-assisted extraction, and then the pure product of UPPP was obtained by purification with AB-8 resin. The bacteriostatic ability of UPPP and the freshness preservation effect on blueberry were analyzed. The results showed that UPPP had a high inhibitory effect on Staphylococcus aureus (MIC of 1.563 mg/mL) and Escherichia coli (MIC of 3.125 mg/mL). Findings revealed that, in comparison to 0.02% potassium sorbate, blueberries treated with a high concentration of UPPP in a dipping treatment displayed superior quality maintenance after 7 days of storage at 4°C. Importantly, analysis of the various metrics showed that treatment with UPPP was significantly better compared to blueberries treated with 0.02% Potassium Sorbate. For example, the decay rate, weight loss, and total number of colonies of blueberries treated with 0.02% Potassium Sorbate were 55.56%, 3.48%, and 4.24±0.07 log CFU/mL, whereas the values of the above indexes for blueberries treated with 25 mg/mL of UPPP were 22.22%, 3.09%, and 3.10±0.17 log CFU/mL, respectively. Conversely, blueberries that were not dipped in any preservative displayed signs of deterioration as early as the 3rd day of the storage period, highlighting the potential of UPPP as a valuable method for preserving fruits and vegetables. Therefore, UPPP holds great promise as an innovative natural food preservative, effectively enhancing food safety, quality, and extending shelf-life.